Awareness for People With Alzheimer’s Disease: Profiles and Weekly Trajectories - Mayelle, Amandine; Hazebrouck, Capucine; El Haj, Mohamad; Mograbi, Daniel C.; Antoine, Pascal (Frontiers in Aging Neuroscience, 2022)
Objective: To understand awareness and fluctuations of awareness in Alzheimer’s disease (AD), it is fruitful to consider the objects of awareness, e.g., cognitive functioning or recognition of the disease, as well as the mechanisms and modes of expression underlying awareness. With a holistic and discourse-centered approach, we aimed to identify different awareness profiles and test whether these profiles were stable or whether transitions from one profile to another occurred over short time intervals. Methods: Twenty-eight residents of nursing homes with a diagnosis of AD participated in four semistructured interviews at biweekly intervals. These interviews were cluster analyzed to determine profiles of awareness. A Markov chain was applied to model their fluctuation. Results: Five awareness profiles were observed that differed in terms of objects and underlying processes. Awareness proved to be quite stable for four of the five profiles. Interindividual variability in awareness was also observed through numerous different trajectories that were identified. Discussion: Self-awareness and disease awareness are characterized by profiles that vary subtly between individuals. Fluctuations in awareness underscore the need to employ assessment intervals that closely reflect daily life in institutions.